ANALYTICAL PROBLEM SOLVING SKILLS AT SOCIAL ARITHMETIC IN PROJECT BASED LEARNING IN GRADE 3 SMP ISLAM ATHIRAH BUKIT BARUGA - Wardah Abubakar (Universitas Negeri Makassar, 2016)
This research is a descriptive qualitative approach which aims to uncover the problem solving ability of junior high school students in project-based learning. The subjects were students of class VII SMP Islam Athirah 3 Bukit Baruga consisting of 25 people. Indicators of problem-solving ability is revealed in this study were (1) the ability to understand the problem, (2) ability to problem-solving plan, (3) ability to carry out the plan, (4) the ability to re-examine the results obtained. The data were analyzed by qualitative content analysis technique with a deductive approach that consists of four stages: preparation, organization, presentation and assessment data. The results of this study were (1) On the indicator of the ability to understand the problem, the ability of students at the high category. Students have no difficulty in writing down the things that are known and asked although generally not written in detail. (2) On the indicator of the ability to plan penyesaian problem, the ability of students in middle category. In writing the students problem-solving plan looks much trouble, generally after they write things that are known and asked them straight into a stage of problem solving. (3) On the indicator of the ability to implement the plan, the ability of students in middle category. Students at this stage are generally able to perform the settlement in accordance with the procedures and rules applicable although some of them are still mengaalami error in the calculation process determines the final answer. (4) On the indicator of the ability to re-examine the results obtained, the ability of students in middle category. Students do activities to examine the results obtained, but there are some among them who only perform checks on the final result without re-check the correctness of each step and calculations performed